Монгол хэлний тогтолцооны гурвал бүрэлдүүлбэр - Д., Бадамдорж (Mongolian Studies, 2023)
In this article, the author found that triple component is in Mongolian language system in the works of Mongolian linguist. The phonological system is the subfoundation of language. It determines the material (phonetical) appearance of its significative units. The lexical system is the whole set of naming means of language, that is, words and stable word-groups. The grammatical system is the whole set of regularities determining the combination of naming means in the formation of utterances as the embodiment of thinking process. The author notes that there is the triple component in linguistics levels such as Mongolian phonetics, phonology, graphemes, stylistics, lexicology, syntax, morphology, semantics, and dialectology. It is said that this is basic concept for research and studies. For example, the vowel of the Mongolian language consists of three dashes: tooth, shin and belly.